2015
DOI: 10.1093/conphys/cov019
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of proteins in pinniped skeletal muscle: viability of post-mortem tissue in physiological research

Abstract: Post mortem tissue from stranded marine mammals is met with skepticism when utilized in biochemical assays. Degradation of muscle proteins and enzymes are not well defined. Given the protected nature and value of diving mammal samples, a quantitative analysis of degradation is valuable and presented here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In addition, although in this case the tissue was collected within 12 h, the timing of tissue collection is of critical importance and might affect the microanatomical structure. A previous study reported that enzymatic activity fluctuates greatly in the first 48 h, depending on storage temperature ( Moore et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although in this case the tissue was collected within 12 h, the timing of tissue collection is of critical importance and might affect the microanatomical structure. A previous study reported that enzymatic activity fluctuates greatly in the first 48 h, depending on storage temperature ( Moore et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%